Origin and distribution of chum salmon Oncorhynchus keta stocks in the western Bering Sea and North-West Pacific in 2009 and 2010 - Alexander V. Bugaev; Roman A. Shaporev; Alexander V. Zavolokin (Известия ТИНРО)
Intraspecific structure of feeding and prespawning aggregations of chum salmon in the western Bering Sea in September-October of 2009 and 2010 and in the North-West Pacific in June-July of 2009 and 2010 is investigated on the data of trawl surveys conducted by Pacific Fish. Res. Center (TINRO) aboard RV Professor Kaganovsky in the framework of the Bering-Aleutian Salmon International Survey, second stage (BASIS-II). In total, 4246 specimens of chum salmon from mixed aggregations were subjected to biological analysis, and for 2462 of them the intraspecific status was identified on the base of scale structure (the scale baseline included the scale data for 11460 chum individuals belonged to 43 local stocks from Asia and North America). Both for the Bering Sea and Pacific Ocean, domination of Russian stocks is defined, contribution of Japanese stocks is significantly lower and lowered comparing with previous years, as 2002-2004 and 2006, and contribution of North American stocks is poor and does not exceed statistical error value of the method. For the western Bering Sea the ratio by countries of the fish origin is the following: Russia 93.8-95.3 %, Japan 2.9-5.2 %, USA 1.0-1.9 % for immature chum salmon in autumn of 2009-2010; and Russia 88.8 %, Japan 9.8 %, USA 1.4 % for maturing chum salmon in autumn of 2009. For the North-West Pacific in summer of 2009-2010, the ratio is similar: Russia 75.4-88.7 %, Japan 10.1-23.9 %, USA 0.7-1.2 % for immature chum salmon; and Russia 81.0-83.0 %, Japan 15.9-17.7 %, USA 1.1-1.3 % for maturing chum salmon. Based on this ratio, the relative abundance of stock complexes by countries of origin is assessed (106 ind.): Russia 107.81-123.32, Japan 3.75-5.98, USA 1.15-2.33 for immature chum salmon in the western Bering Sea in 2009 and 2010; Russia 6.34, Japan 0.70, USA 0.10 for maturing chum salmon in the western Bering Sea in 2009; Russia 19.27-37.74, Japan 6.11-4.30, USA 0.18-0.51 for immature chum salmon in the North-West Pacific in 2009 and 2010; and Russia 29.02-42.60, Japan 5.56-9.31, USA 0.38-0.68 for maturing chum salmon in the North-West Pacific in 2009 and 2010. For the immature chum salmon in the North-Western Pacific, the assessments of intraspecific composition and relative abundance of different groups should be considered as preliminary results, because of insufficient number of the scale samples.